2018
DOI: 10.2478/jec-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Social Behavior of Schoolteachers of Latvia and Russia in the Structure of Teacher Professional Identity

Abstract: The article presents the results of the international study of the professional identity of schoolteachers of Russia and Latvia. In the study, the six component model of the content of the teacher professional identity (TPI) is used. According to this model, in 2017, the questionnaire “School Teacher Professional Identity” was created and international survey organized, in which 437 schoolteachers from Latvia and the Smolensk region of Russia participated. The aim of this article is to analyze the data of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The social behaviour of teachers, often known as good character, may indirectly influence academic achievements (Shah, 2009b;Shahmohammadi, 2014). An empirical study by Jermolajeva et al (2019) showed that the social behaviour of teachers is positively correlated with their effective professional work. Ađalsteinsdóttir (2004) has stressed the importance for teachers to recognize and understand their own behaviour because it has a significant effect on the students' educational and social development.…”
Section: The Social Behaviours Of Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…The social behaviour of teachers, often known as good character, may indirectly influence academic achievements (Shah, 2009b;Shahmohammadi, 2014). An empirical study by Jermolajeva et al (2019) showed that the social behaviour of teachers is positively correlated with their effective professional work. Ađalsteinsdóttir (2004) has stressed the importance for teachers to recognize and understand their own behaviour because it has a significant effect on the students' educational and social development.…”
Section: The Social Behaviours Of Teachersmentioning
confidence: 99%
“…The concept of teacher professional identity has been studied comprehensively, so it has become a separate field for educational research (Akkerman & Meijer, 2011;Beijaard et al, 2004). One of its most important constructs, the social behaviour of teachers, has been claimed as an important identifier for measuring the influence and the professional performance of teachers (Jermolajeva et al, 2019) In this, our research study we proposed that the social behaviour of teachers can be influenced by external factors such as (1) training in social behaviour, (2) exposure to an environment where certain social behaviour is reinforced, and/or most importantly (3) the leadership competence of the school principal.…”
Section: Introductionmentioning
confidence: 99%
“…In the Latvian context, up to date research-based evidence showing that teachers are equipped with the necessary competence and appropriate support in the context of these curriculum changes is limited. Educational researchers in Latvia have been focusing on topics such as in-service and pre-service teacher professional identity (Ivanova & Skara-Mincāne, 2016;Jermolajeva, Bogdanova, & Silchenkova, 2018), pre-service teachers (Daniela, Strods, Rubene, & Kalniņa, 2018), formation of teacher professional learning communities (Geske & Rečs, 2019) or school principals (for a review see Bluma & Daiktere, 2016). To our knowledge, in the context of new education changes such as teaching and learning 21 st century skills there have not been empirical research on new approaches to teacher as employee competence management that would be school-based and with direct involvement from the school leaders.…”
Section: Piloting a Teacher Competence Management Model In Schools Inmentioning
confidence: 99%